Kaposi’s Sarcoma-Associated Herpesvirus Encodes a bZIP Protein with Homology to BZLF1 of Epstein-Barr Virus - Lin, Su-Fang (American Society for Microbiology, 1999)
Kaposi’s sarcoma-associated herpesvirus (KSHV) is a recently discovered human gamma herpesvirus strongly implicated in AIDS-related neoplasms. We report here the identification in the KSHV genome of a gene for a protein designated K-bZIP and belonging to the basic-leucine zipper (bZIP) family of transcription factors. K-bZIP shows significant homology to BZLF1, which plays a key role in the replication and reactivation of Epstein-Barr virus. K-bZIP is a homodimerizing protein of 237 amino acids with a prototypic bZIP domain at the C terminus. The N-terminal portion of K-bZIP is derived from the K8 open reading frame which, through in-frame splicing, adjoins the ZIP domain. This structure was revealed by rapid analysis of cDNA ends, followed by cloning of the entire cDNA. A 1.35-kb transcript encoding K-bZIP was detected in BCBL-1 cells treated with 12-O-tetradecanoylphorbol-13-acetate. The synthesis of this transcript was blocked by the protein synthesis inhibitor cycloheximide but not by the viral DNA synthesis inhibitor phosphonoacetate, a result which classifies it as an early lytic gene. RNase protection analysis further mapped the major transcription start site for the 1.35-kb K-bZIP mRNA and identified two other splice variants which encode proteins with the N-terminal portion of K-bZIP but lacking the C-terminal ZIP domain. Full-length K-bZIP forms dimers with itself, and the C terminus encompassing the ZIP domain is required for this process. Our studies set the stage for understanding the role of K-bZIP in the replication and reactivation of the KSHV genome.